a) Chứng minh (x+y+z)^2 = x^2 + y^2 + z^2 + 2xy + 2yz + 2zx
Bắt đầu từ vế trái của đẳng thức:
(x+y+z)^2 = (x+y+z)(x+y+z)
= x(x+y+z) + y(x+y+z) + z(x+y+z)
= x^2 + xy + xz + xy + y^2 + yz + xz + yz + z^2
= x^2 + 2xy + 2xz + y^2 + 2yz + z^2
= x^2 + y^2 + z^2 + 2xy + 2yz + 2zx
Như vậy, đẳng thức (x+y+z)^2 = x^2 + y^2 + z^2 + 2xy + 2yz + 2zx đã được chứng minh.
b) Chứng minh (x+y+z)^3 = x^3 + y^3 + z^3 + 3(x + y)(y + z)(z + x)
Bắt đầu từ vế trái của đẳng thức:
(x+y+z)^3 = (x+y+z)(x+y+z)(x+y+z)
= (x+y+z)((x+y+z)^2)
= (x+y+z)(x^2 + y^2 + z^2 + 2xy + 2yz + 2zx)
= x(x^2 + y^2 + z^2 + 2xy + 2yz + 2zx) +
y(x^2 + y^2 + z^2 + 2xy + 2yz + 2zx) +
z(x^2 + y^2 + z^2 + 2xy + 2yz + 2zx)
= x^3 + x^2y + x^2z + 2x^2y + 2xy^2 + 2xyz +
xy^2 + y^3 + y^2z + 2xy^2 + 2xyz + 2yz^2 +
xz^2 + yz^2 + z^3 + 2x^2z + 2xyz + 2yz^2
= x^3 + y^3 + z^3 + 3x^2y + 3xy^2 + 3y^2z + 3yz^2 + 3z^2x + 3xz^2
= x^3 + y^3 + z^3 + 3xy(x + y) + 3yz(y + z) + 3zx(z + x)
= x^3 + y^3 + z^3 + 3(x + y)(y + z)(z + x)
Như vậy, đẳng thức (x+y+z)^3 = x^3 + y^3 + z^3 + 3(x + y)(y + z)(z + x) đã được chứng minh.